The future of CNVs: sequence based resolution and links to human disease 2 - Eichler, Evan (Henry Stewart Talks, 2009)
Future discovery of CNVs, Genotyping, Inversion and deletion, 17q21.31 targeted sequencing, Application of next-generation sequencing technology, Personalized duplication or CNV map, Long read sequencing technology, Single-molecule, real-time detection of structural variation (SMRT-SV), Full-spectrum of human genetic variation
Updated at 2017/03/29